EFEKTIVITAS PELAKSANAAN PROGRAM MIKROFINANCE PERTANIAN OLEH CU CINTA KASIH KELURAHAN PULO BRAYAN KECAMATAN MEDAN BARAT - Johannes Arif Manata Sirait (Welfare StatE, 2012)
The biggest difficulty of farmers in developing their farm is getting the capital. They were forced to use the service of money lenders or provate cooperations that burden them with enormous interest that they get stuck into the cycle of poverty. They need an agency, that can help them to get the capital in the form of loans with mild interest. In regard to this problem, CU Cinta Kasih attends with a program which is named  agricultural microfinance. It is specially designed to provide capital. CU Cinta Kasih also implemented the poverty lending approach, which gave supporting activities such as education and training to its members. The research was conducted at CU Cinta Kasih Pulo Brayan West Medan District to measure how far the agricultural microfinance program is effective in providing capital to its members. The results of this research showed that agricultural microfinance program by CU Cinta Kasih is very helpful in providing capital to develop their farm. But, in supporting activities such as education, demoplot, discussions etc have not run maximally. Keywords: Effectiveness, Coorperation, Agricultural Microfinance Program, The Poverty Lending Approach